Construction of lean control system of prefabricated mechanical building cost based on Hall multi-dimensional structure model (Informatica, 2022)
Based on the systematic idea of Hall multidimensional structure and the theory and practice of prefabricated building cost lean management, the prefabricated mechanical building cost lean control system based on Hall multidimensional structure model is proposed and constructed.The application of the lean management of hall multidimensional structure model from the perspective of time dimension, logic and knowledge dimension. The example analysis results show that the original design components and the number of open modes are 72, the optimized types of components and the number of open modes are 51, reduce 21 mold machining, mold costs were reduced by about 25%. The number of original design components and the lifting times of components are 129 kinds, the number of components and lifting of components are 103, the number of components per layer was decreased by 26, lifting time is shortened by about 20%, comprehensive construction period is shortened by more than 40 days, improve the management efficiency, lean cost control of the project plays a positive role.It provides reference for the lean control system management of hall multidimensional structural model.